2012 IEEE International Conference on Communications (ICC) 2012
DOI: 10.1109/icc.2012.6364339
|View full text |Cite
|
Sign up to set email alerts
|

Combination weights for diffusion strategies with imperfect information exchange

Abstract: Adaptive networks rely on in-network and collaborative processing among distributed agents to deliver enhanced performance in estimation and inference tasks. Information is exchanged among the nodes, usually over noisy links. This paper first investigates the mean-square performance of adaptive diffusion algorithms in the presence of various sources of imperfect information exchanges and quantization errors. Among other results, the analysis reveals that link noise over the regression data modifies the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Although we can continue our analysis by studying this general case in which the vectors z i do not have zero-mean (see [62,63]), we shall nevertheless limit our discussion in the sequel to the case in which there is no noise during the exchange of the regression data, i.e., we henceforth assume that:…”
Section: Error Recursionmentioning
confidence: 99%
“…Although we can continue our analysis by studying this general case in which the vectors z i do not have zero-mean (see [62,63]), we shall nevertheless limit our discussion in the sequel to the case in which there is no noise during the exchange of the regression data, i.e., we henceforth assume that:…”
Section: Error Recursionmentioning
confidence: 99%
“…where ℛ υ p collects all covariance matrices ℛ υ, rk p corresponding to the evaluated price data noise [v k (i)] k ∈ K throughout the diffusion network. It is shown in [44,46] that minimising the upper bound of the network MSD and EMSE for Algorithm 2 over left-stochastic combination matrices D leads to the following relative variance rule:…”
Section: Robustness Analysismentioning
confidence: 99%
“…We showed that the mean‐square stability of Algorithm 2 is independent of the combination weights and topology. However, is it shown in [44] that link noise and imperfect information exchange over the regression data (price signal scriptP) modifies the dynamics of the network evolution, and leads to biased estimates in steady‐state, deteriorating the performance of the proposed solution. The analysis also reveals how the network mean‐square performance is affected by modifying weight matrices [44].…”
Section: Diffusion Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The works [5]- [7], [9]- [12] show that noisy exchanges result in performance degradation of distributed strategies. Then, in order to counter the effect of such degradation, resilient distributed schemes are developed in [5]- [7], [9], [12]- [17].…”
Section: Introductionmentioning
confidence: 99%